Research and Experimental Diagnostics of Intelectual Level of Primary School Pupils at Natural History Lessons - Anastasia Kinesheva (Pedagogical Discourse, 2012)
The results of research and experimental diagnostics of the intellectual level of primary school children at natural history lessons by means of the problem testing are offered.